Directional tuning during reach planning in the supramarginal gyrus using local field potentials. (June 2019) - Barbaro, Michael F.; Kramer, Daniel R.; Nune, George; Lee, Morgan B.; Peng, Terrance; Liu, Charles Y.; Kellis, Spencer; Lee, Brian
Highlights: Motor cortex spectral changes while reaching match inferior parietal while planning. Local field potentials can be used for directional tuning in a human subject. Inferior parietal cortex shows directional tuning while planning a reach. Abstract: Previous work in directional tuning for brain machine interfaces has primarily relied on algorithm sorted neuronal action potentials in primary motor cortex. However, local field potential has been utilized to show directional tuning in macaque studies, and inferior parietal cortex has shown increased neuronal activity in reaching tasks that relied on MRI imaging. In this study we utilized local field potential recordings from a human subject performing a delayed reach task and show that high frequency band (76–100 Hz) spectral power is directionally tuned to different reaching target locations during an active reach. We also show that during the delay phase of the task, directional tuning is present in areas of the inferior parietal cortex, in particular, the supramarginal gyrus.